2015
DOI: 10.5194/hessd-12-2799-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Accelerated gravity testing of aquitard core permeability and implications at formation and regional scale

Abstract: Abstract. Evaluating the possibility of leakage through low permeability geological strata is critically important for sustainable water supplies, the extraction of fuels from strata such as coal beds, and the confinement of waste within the earth. The current work demonstrates that relatively rapid and reliable hydraulic conductivity (K) measurement of aquitard cores using accelerated gravity can inform and constrain larger scale assessments of hydraulic connectivity. Steady state fluid velocity through a low… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Investigations of a 31 m deep clayey silt paleovalley fill from Cattle Lane, Australia (Acworth et al, ), have revealed the potential for hydraulically active flow paths. Geotechnical centrifuge techniques (Crane et al, ; Timms et al, ) found that vertical K varied between 1.4×108 and 1.1×1010 m/s with a geometric mean value of 4.2×109 m/s (13 samples, 5–31.4 m BGL), values that were consistent with in situ vertical K values (Timms & Acworth, ). The vertical K values are high for an aquitard (as defined by K of 1081016 m/s; Neuzil, ) and have prompted more detailed investigation into the depositional properties and groundwater processes at this site.…”
Section: Introductionmentioning
confidence: 56%
See 4 more Smart Citations
“…Investigations of a 31 m deep clayey silt paleovalley fill from Cattle Lane, Australia (Acworth et al, ), have revealed the potential for hydraulically active flow paths. Geotechnical centrifuge techniques (Crane et al, ; Timms et al, ) found that vertical K varied between 1.4×108 and 1.1×1010 m/s with a geometric mean value of 4.2×109 m/s (13 samples, 5–31.4 m BGL), values that were consistent with in situ vertical K values (Timms & Acworth, ). The vertical K values are high for an aquitard (as defined by K of 1081016 m/s; Neuzil, ) and have prompted more detailed investigation into the depositional properties and groundwater processes at this site.…”
Section: Introductionmentioning
confidence: 56%
“…Steady state K measurements of core subsamples taken from 5.0, 9.5, and 21.8m depth BGL (below ground level) were reported by Crane et al () and Timms et al (). Details are provided on steps to ensure reliable K measurements of intact samples (Crane et al, ; Timms et al, ), primarily related to core storage, stress application and detection of rapid leakage. Potential errors were evaluated and minimized for example, by using relatively large diameter cores (101.6 mm) and application of stresses less than or equivalent to in situ stresses at the depth of core collection.…”
Section: Methodsmentioning
confidence: 67%
See 3 more Smart Citations